2013
DOI: 10.1186/1748-717x-8-228
|View full text |Cite
|
Sign up to set email alerts
|

Prostate stereotactic body radiotherapy with simultaneous integrated boost: which is the best planning method?

Abstract: BackgroundThe delivery of a simultaneous integrated boost to the intra-prostatic tumour nodule may improve local control. The ability to deliver such treatments with hypofractionated SBRT was attempted using RapidArc (Varian Medical systems, Palo Alto, CA) and Multiplan (Accuray inc, Sunnyvale, CA).Materials and methods15 patients with dominant prostate nodules had RapidArc and Multiplan plans created using a 5 mm isotropic margin, except 3 mm posteriorly, aiming to deliver 47.5 Gy in 5 fractions to the boost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 47 publications
3
20
0
Order By: Relevance
“…Hegazy et al, (2016) found that all dose constraints regarding PTV coverage were similarly achieved by both plans generated by the RA and CK except for the maximal doses generated by the RA plans which were statistically significant lower than those of the CK plans. Tree et al, (2013) have shown that RA and CK can produce clinically acceptable plans. Macdougall et al, (2014) showed no distinct dosimetric advantage to choose CK over RA and also found that CK failed to achieve the desired PTV homogeneity constraint in two cases.…”
Section: Discussionmentioning
confidence: 99%
“…Hegazy et al, (2016) found that all dose constraints regarding PTV coverage were similarly achieved by both plans generated by the RA and CK except for the maximal doses generated by the RA plans which were statistically significant lower than those of the CK plans. Tree et al, (2013) have shown that RA and CK can produce clinically acceptable plans. Macdougall et al, (2014) showed no distinct dosimetric advantage to choose CK over RA and also found that CK failed to achieve the desired PTV homogeneity constraint in two cases.…”
Section: Discussionmentioning
confidence: 99%
“…The rectum dose reduction we have seen between patients planned with ERB and noERB is a meaningful finding in the context of extreme hypofractionated CyberKnife prostate SBRT of 36.25 Gy in five fractions. These results and the effective plan optimization technique may turn out to be even more important in view of the more recent interests in prostate focal therapy approach by generating a simultaneously integrated dose escalation to 47.5 Gy onto the dominant intra‐prostatic lesion while maintaining the 36.25 Gy to the prostate gland …”
Section: Discussionmentioning
confidence: 99%
“…Most studies to date have used static field IMRT [14,[19][20][21][22][23]. Planning studies have also assessed VMAT [24][25][26] and SBRT techniques [27,28]. Also unclear is which groups of patients would benefit from an intraprostatic boost.…”
Section: Dose Paintingmentioning
confidence: 99%
“…Adequate margins must be added to take into account co-registration and delineation errors plus motion during the treatment course (intra-and interfraction motion). Even taking into account the margin required to cover the IPL adequately, given the discrepancy seen with delineation as discussed earlier, the optimal intraprostatic margin for the boost is unclear and is dependent on the mode of delivery with some studies using a 0mm margin and relying on a relatively shallow dose fall off within the prostate CTV [19,23,24,28]. Treatment must be delivered accurately with the use of in-room IGRT, with fiducial markers as the current gold standard.…”
Section: Implementation Of Tumour Dose-escalationmentioning
confidence: 99%